From Revelation to Resilience: Qur’anic Ethics in Family Life and Their Role in Addressing Youth Moral Disruption - Siti Asiyah Dalimunthe,; Pradana, Satria Adi; Drajat, Amroeni; Nasution, Muhammad Roihan (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2025)
The rapid integration of digital technology into daily life has significantly altered social behavior and moral norms, particularly among adolescents. This transformation has raised concerns about moral degradation within Muslim youth communities. This study investigates the relevance of Qur’anic character education in the family as a strategic response to these challenges. Employing a qualitative library research approach, the study analyzes primary and secondary sources—including Qur’anic exegesis and contemporary Islamic educational literature. Selected verses—Surah Luqman [31]: 12–19, Surah Maryam [19]: 30–34, Surah Al-An’am [6]: 151–153, Surah Al-Isra’ [17]: 23–24, and Surah Al-Hujurat [49]: 11–12—highlight core ethical principles such as gratitude, honesty, humility, and social responsibility. The findings reveal that when these values are instilled through family-based education, they form a resilient ethical framework capable of mitigating the disruptive moral effects of digital media. Qur’anic moral teachings serve as a cultural bridge across generations, reinforcing ethical awareness and preserving religious identity. The study calls for renewed attention to intra-family Qur’anic education as a vital form of cultural resistance and moral resilience in the digital era